Rapid Assessment of the Neonate With Sonography (RANS) Scan. (23rd September 2018) - Safarulla, Azif; Kuhn, Walter; Lyon, Matthew; Etheridge, Rebecca J.; Stansfield, Brian; Best, Graciela; Thompson, Amy; Masoumy, Emily; Bhatia, Jatinder
Abstract : The use of point‐of‐care sonography in clinical settings such as emergency medicine and intensive care units has increased, but adoption in neonatology has been slow. Unlike the focused assessment with sonography for trauma scan used in adults, a quick bedside scan to rapidly evaluate an acutely deteriorating neonate does not exist. The objective of our article is to introduce a focused bedside ultrasound scan that is easy to learn, rapidly performed, and relatively inexpensive.© 2018 by the American Institute of Ultrasound in Medicine